The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1037/0022-0167.36.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Integrating research on the microcounseling program: A meta-analysis.

Abstract: Subjected research on Ivey's (1971) microcounseling program to a comprehensive meta-analytic review. A multistage sampling procedure resulted in the identification of 81 admissible studies. Glass's (1976) effect size (ES) statistic was used to estimate average effects for each study and across all studies, and the relation between ES and the sampling distribution of several important methodological and substantive characteristics was assessed. The most conservative overall ES statistic fell in the large-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
2
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 58 publications
6
83
2
2
Order By: Relevance
“…The research conducted so far has focused on evaluating the educational benefits of communication skills training (cf., Baker and Daniels 1989;Baker et al 1990;McLennan 1994) and the impact of discrete counselor behaviors on specific counseling processes (cf., Hill 2001). This research has been primarily of an analogue nature and has not linked delivery of particular counseling skills to validated measures of client improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research conducted so far has focused on evaluating the educational benefits of communication skills training (cf., Baker and Daniels 1989;Baker et al 1990;McLennan 1994) and the impact of discrete counselor behaviors on specific counseling processes (cf., Hill 2001). This research has been primarily of an analogue nature and has not linked delivery of particular counseling skills to validated measures of client improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Yet though reasonable, research has not yet established the therapeutic benefits of basic attending and listening skills in the context of very short-term counseling. While it is has been demonstrated that basic attending and listening skills can be acquired and even retained by counseling students (e.g., Baker and Daniels 1989;McLennan 1994), little research has attempted to link delivery of these specific skills to validated outcomes with actual clients (e.g., Roffers et al 1988). In fact, nearly all of the studies attesting to the value of very brief therapy (1-3 sessions) are based on solution-focused therapy or some derivative thereof (cf., Bloom 2001;Miller 2008;Perkins and Scarlett 2008;Talmon 1990); models in which problem exploration is explicitly eschewed in favor of quickly working toward solutions to clients' most pressing problems.…”
Section: Termination Stagementioning
confidence: 98%
“…Wells, Hawkins, and Catalano (1988), in their review of outcome studies of drug usage, found 25 distinct procedures and measures to assess drug use. And in a related area, Baker and Daniels (1989) reported a meta-analysis of microcounseling programs aimed at changing counselor behavior. In the 81 studies included in the analysis, 82 different dependent measures were used at least once; 72 were used in only one or two studies.…”
Section: Historical Overview and Current Statusmentioning
confidence: 98%
“…Desafortunadamente, las revisiones de los últimos 20 años (Alberts y Edelstein, 1990;Baker y Daniels, 1989, 1990Elliott, 2001;Hill y Lent, 2006;Lambert y Barley, 2001), concluyen que: a) la defi nición y mecanismos de la empatía parecen no estar claros (Sexton y Whiston, 1994); b) los resultados de investigación han generado "poco acuerdo entre los investigadores" (Moore, 1990); c) esto se debe a las diferencias teóricas existentes al defi nir la empatía, y a los problemas metodológicos que emergen a la hora de su evaluación (Duan, y Hill, 1996;Bohart et al, 2002).…”
Section: Introductionunclassified